MLTI-03. FIRST-LINE STEREOTACTIC RADIOSURGERY COMBINED WITH SYSTEMIC TARGETED AND IMMUNE CHECKPOINT INHIBITOR THERAPY IN MELANOMA PATIENTS WITH NEWLY DIAGNOSED BRAIN METASTASES. (12th August 2019) - Heumann, Thatcher; Ye, Rebecca; Wu, Peter; Habibi, Akram; Sansosti, Alexandra; Beaudreault, Cameron; Kryger, Marc; Bernstein, Kenneth; Pavlick, Anna; Kondziolka, Douglas
Abstract: BACKGROUND: Of solid tumors, melanoma has the highest propensity for CNS spread with historic median survivals of 5–8 months following brain metastasis diagnosis. We evaluated the impact of systemic BRAF targeted and immune checkpoint inhibitor (ICI) therapies on survival outcomes in patients receiving stereotactic radiosurgery (SRS) for melanoma brain metastases (MBM) and assessed patient treatment burden associated with prolonged survival. METHODS: We retrospectively reviewed the demographics, disease characteristics, therapeutic regimens, overall survival, and first-year cumulative incidence of comorbid disease for patients with de novo MBM treated between 2013 and 2017 at a major melanoma referral center. RESULTS: Among 123 newly diagnosed MBM patients: 65% were male, 24% were 50 years old or less, 50% were BRAF mutated, 63% had multiple intracranial lesions at diagnosis. Locally, 73% received SRS as first-line treatment. Systemically, 73% received ICI, 46% received BRAF targeted therapy, and 12% received neither. With a median follow up of 11 months (mo), total cohort median OS was 13.2 mo. Median OS for first-line SRS combined with ICI and BRAF targeted therapy was 31.0 mo (47% 3-year OS), 17.5 mo (31% 3-year OS) with ICI monotherapy, and 6.1 mo (22% 3-yr OS) alone. SRS and BRAF targeted therapy were associated with improved OS. At one-year follow-up, comorbid conditions with the greatest cumulative incidence were fatigue, nausea, intracranial hemorrhage, deep vein thrombosis, major depressive disorder, and pneumonia. Patients averaged one inpatient visit every 4.5 mo (1 week average length of stay), and 2 advanced imaging studies (MR/CT/PET-CT) per month following MBM diagnosis. CONCLUSIONS: In one of the largest reported MBM series, survival has improved markedly for patients receiving first-line SRS combined with targeted and immunotherapies. Simultaneously, longer life expectancy comes with increasing incidences of comorbid conditions reflecting an evolving complexity of and need for coordination of care for patients with MBM.